Comparative studies on nutritional quality of commercial wheat flour in Bangladesh - Saeid, A; Hoque, S; Kumar, U; Das, M; Muhammad, N; Rahman, MM; Ahmed, M (Bangladesh Journal of Scientific and Industrial Research, 2015)
Cereal industry and its derived products have a large economic and social importance worldwide. Baking industries are extensively using wheat flour to produce various baked products. Therefore, in this investigation it is intended to study and determine proximate, physicochemical, functional properties of six brand of wheat flour in Bangladesh. The entire brand had moisture contents: 9.90-12.48%, protein: 8.67-12.47%, fat: 0.893-1.387% and ash content: 0.387-0.707%. The ACI brand had the highest amount of protein of 12.47% whereas Romoni brand had highest fat of 1.387%, fiber: 0.26%, gluten content: 15.34% and water absorption index of 1.9 g/g as compared to other brands. In addition, sodium and calcium content were higher in ACI brand whereas potassium content was higher in Romoni brand. Results showed that wheat flour from all brand could be used to make various type of baked products. Bangladesh J. Sci. Ind. Res. 50(3), 181-188, 2015